The role of middle frontal gyrus in working memory retrieval by the effect of target detection tasks: a simultaneous EEG-fMRI study - Xu, Ping; Wang, Min; Zhang, Tingting; Zhang, Junjun; Jin, Zhenlan; Li, Ling (Brain Structure and Function, 2024)
Maintained working memory (WM) representations have been shown to influence visual target detection selection, while the effect of the visual target detection process on WM retrieval remains largely unknown. In the current research, we used the dual-paradigm of the visual target detection task and the delayed matching task (DMT), which contained the following four conditions: the match condition: the DMT target contained the detection target; the mismatch condition: the DMT target contained the detection distractor; the neutral condition: only the detection target was presented; the catch condition: only the DMT target was presented. Twenty-six subjects were recruited in the experiment with simultaneous EEG-fMRI data. Behaviorally, faster responses were found in the mismatch condition than in the match and neutral conditions. The EEG data found a greater parieto-occipital N1 component in the mismatch condition compared to the neutral condition, and a greater frontal N2 component in the match condition than in the mismatch condition. Moreover, compared to the match and neutral conditions, weaker activations of the bilateral middle frontal gyrus (MFG) were observed in the mismatch condition. And the representational similarity analysis (RSA) revealed significant differences in the representational patterns of the bilateral MFG between mismatch and match conditions, as well as in the representational patterns of the left MFG between mismatch and neutral conditions. Additionally, the left MFG may be the brain source of the N1 component in the mismatch condition. These findings suggest that the mismatch between the DMT target and detection target affects early attention allocation and attentional control in WM retrieval, and the MFG may play an important role in WM retrieval by the effect of the target detection task. In conclusion, our work deepens the understanding of the neural mechanisms by which visual target detection affects WM retrieval.